Synthesis of Ultrathin PdCu Alloy Nanosheets Used as Highly Efficient Electrocatalyst for Formic Acid Oxidation - Yang, Nailiang (2017)
Inspired by the unique properties of ultrathin 2D nanomaterials and excellent catalytic activities of noble metal nanostructures for renewable fuel cells, a facile method is reported for the high-yield synthesis of ultrathin 2D PdCu alloy nanosheets under mild conditions. Impressively, the obtained PdCu alloy nanosheet after being treated with ethylenediamine can be used as a highly efficient electrocatalyst for formic acid oxidation. The study implicates that the rational design and controlled synthesis of an ultrathin 2D noble metal alloy may open up new opportunities for enhancing catalytic activities of noble metal nanostructures.